Impact of 5R Culture on Employee Performance in HSE Department Using Multiple Linear Regression - Badriah, Siti; Fitriani, Risma; Sumitra, Naufal Rabbani (Jurnal Serambi Engineering, 2026)
The Department of Health, Safety, and Environment (HSE) has a strategic role in ensuring occupational safety, health, and environmental protection, especially in B3 waste management. However, in practice, problems such as low work efficiency, a less organized work environment, and non-compliance with safety procedures are still found. One approach that can be applied to overcome this problem is the 5S work culture (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). This study aims to analyze the influence of 5S culture on the activities of HSE Department employees at PT Trigunapratama Abadi. The research uses a quantitative approach with a descriptive and verifiable design. Primary data were obtained through a Likert scale questionnaire distributed to HSE employees and analyzed using multiple linear regression with the help of SPSS software. The results showed that simultaneously the 5S culture did not have a significant effect on employee activities, with a significance value of the F test of 0.701. Partially, each of the 5S variables also did not show a significant influence on employee activities. A determination coefficient value (R Square) of 0.397 indicates that the 5S culture is able to explain 39.7% of the variation in employee activities, while the rest is influenced by other factors outside the study model. Nevertheless, the implementation of the 5S culture remains important as the basis for the formation of orderly, disciplined, and safety-oriented work behavior.